Enhancing Student’s English Linguistic, Social and Digital Competences through Blended Learning - Kristiana Kusnadi, Jevinda; Nursukma Rahmatani, Siti; Kintan Puteri Laudhisa, Katarina; Elina; Hendar (International Journal of Psychosocial Rehabilitation, 2020)
To build learning competency in the era of industrial revolution 4.0, blended learning, a method that combines face-to-face with on-line learning becomes an interesting approach to use in learning English. This learning model aims to change the culture of learning- a teaching which is centered on the teacher-centered learning(TCL) to student-centered learning (SCL). The main purpose of this study is, therefore, to find out how blended learning can (1) improve students' linguistic competencies; (2) improve students' social competencies; and (3) improve students' digital competencies. The research was conducted for the students of Da'wah and Sharia Faculties in Bandung Islamic University. The students were firstly given the pre-test, then they studied English Grammar face to face for 5 times. Then, they did the group activities to make a task in the form of a Vlog; and finally they were given the activities by using internet services and application to learning English, Edmodo. Using action research, the results showed that students' linguistic competencies given through face-to-face activities were significant as indicated by the results of their tests. The students' social competencies through group work showing the role division of each individual where they had to make Vlogs was considered very positive; and students' digital competencies through Edmodo showed excellent feedbacks, measured by the results of evaluations that were made through the application as well. Overall it can be concluded that through the Blended Learning method, students' linguistic, social and technology /digital competences significantly increased.